The relevance of prehistoric rock art in the present (Journal for Studies in Humanities and Social Sciences, 2019)
Today the rock art of southern Africa enjoys worldwide appreciation, which is based on several factors: Certainly the art of various regions on the subcontinent responds to the aesthetic predilection of a wide, mainly western audience; this phenomenon is enhanced by tourists who add some cultural flavour to their travels that usually aim at the nature and wildlife of southern Africa. In a synchronic development, indigenous people began to re-define their relation to the art and appropriated it in various new ways. Today they are more explicit about their ontological association with the art, partly claiming more or less direct descent from the earlier artists (such as in Tsodilo). Moreover they accept that people made the pictures, an attitude that was less common a few decades ago when San, questioned about authorship of the art, maintained that people cannot paint this way but only the Great God can. This paper explores the connection between local communities and rock art in Southern Africa. It uses examples from Botswana, Namibia, South Africa and Zimbabwe to argue and demonstrate that rock art is no longer the preserve of western sciences and tourism alone but that through appropriation the art has multiple motivations from spiritual to identity issues, and claims of land ownership to economic benefit.